ROLE OF KUMARI(ALOE VERA CHINENSIS) IN RASASHASTRA AND BHAISHAJYAKALPANA - Jadhav Kalyani K. (International Journal of Applied Ayurved Research, 2016)
Kumari has very important role in Rasashastra bhaishajyakalpana,because it plays an im-portant role in Shodhana,Bhasmaprakriya,Amrutikaran and formulations.Bhavana of Kumari has mentioned for Kupipakwarasayan,Pottalirasayan & khalvirasayana.Bhavana of Kumariswarasa is told for all Sudhavargbhasmikaran process.Some bhasmas are harmful i.e.Tamrabhasma,Suvarnamakshikbhasma etc. So after Bhasmaprakriya Amrutikaran Samskara is done, to remove its Apakwadosha (incomplete burnt impurities). Kumari is mostly used for Amruikaran.. Aloe vera is found in North Afrika, America,Spain. & India. The leaves contain juice reffered to as aloe. The juice is obtained by two methods. 1) Juice is placed in sunlight & dried. It is non transparent 2) Juice is dried in rapid fire .It is transparent. Indian Aloe vera has three varities, 1)AloeChinensis Baker is found in south India. 2) Aloe LittoralisKoeingex Baker is found in Madras. 3) Aloe Variegata Linn. Is found in Maharashtra. Chemical composition Aloe Emodin,aloctin A(Glycoprotein),aloenin,(bitter glucoside) barbaloin,chrysophanol,glycoside,galactose,mannose,aldopentose,aloesin,aloesone,B-sitosterol,alocutin A&B